2021
DOI: 10.1016/j.jss.2020.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Outcomes for Patients and Providers After Elective Tracheostomy in COVID-19–Positive Patients

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 18 publications
2
18
0
3
Order By: Relevance
“…SD, standard deviation; BMI, body-mass index; PEEP, positive end-expiratory pressure; APACHE II, Acute Physiology and Chronic Health Evaluation II. Characteristic Value References Count n(%) Total patients 3929 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 3929 (100) Sex n (%) Female Male 437 (27.01) 1181 (72.99) 23 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , ...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…SD, standard deviation; BMI, body-mass index; PEEP, positive end-expiratory pressure; APACHE II, Acute Physiology and Chronic Health Evaluation II. Characteristic Value References Count n(%) Total patients 3929 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 3929 (100) Sex n (%) Female Male 437 (27.01) 1181 (72.99) 23 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , ...…”
Section: Resultsmentioning
confidence: 99%
“…37 studies included mortality data, irrespective of subgrouping. Of the 3876 patients included across these 37 studies, 824 patients had died by the time of follow-up [24][25][26][27][28][29][30][31][32][33][35][36][37][38][39][40][41][41][42][43][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] . Only 14 studies explicitly reported a mean follow-up duration, giving a combined weighted mean of 42.03 days (SD 26.43) 24,26,27,30,33,37,42,43,48,50,52,56,…”
Section: Mortalitymentioning
confidence: 99%
See 3 more Smart Citations